Availability of Analgesic and Anti-Inflammatory Medicines in Primary Health Care - Jacqueline Silva Santos; Alex Junio Silva da Cruz; Lia Silva de Castilho; Mauro Henrique Nogueira Guimarães Abreu (Association of Support to Oral Health Research (APESB), 2022)
Objective: To describe and analyze the availability and factors related to the presence of analgesics and non-steroidal anti-inflammatory drugs in the Brazilian public primary healthcare system. Material and Methods: This was a cross-sectional study that evaluated 17,903 health units that participated in the National Program for Primary Care Access and Quality Improvement (2013-2014). The dependent variable was defined as the presence of metamizole, ibuprofen, and acetaminophen in a sufficient amount. The independent variables included the type of primary health care unit, the presence of a medication disposal area, the number of physicians, nurses, and dental practitioners; and the number of primary care units with family and oral health teams. For statistical analysis, unadjusted and adjusted Odds Ratio (OR) (95% CI) were presented. Results: The three medicines were available in 62.4% of the units. Regarding Health Clinics, the Basic Health Units (OR= 1.31, CI95% 1.18-1.44), Polyclinic (OR= 2.00, 95% CI, 1.15 -3.48), and others (OR= 1.37; 95% CI 1.14-1.63) had higher chances of availability of all three drugs. The presence of a disposal area (OR = 1.64, 95% CI 1.51-1.77) and the number of physicians (OR= 1.04, 95% CI 1.00-1.08), nurses (OR= 1.08, 95% CI 1.03- 1.13), and dental practitioners (OR= 1.09, 95% CI 1.04-1.14) increased the availability odds of the analyzed drugs in the service. Conclusion: The structure of the healthcare units and the higher number of professionals were positively associated with the availability of these drugs.